Design and development of a pneumatic accelerator and its application on high speed blanking - Chan, Lin Tak. (2008)
Design and development of a device called Pneumatic Accelerator to convert the low speed operation of the ram of a mechanical press to high speed operation of a ram using a differential piston arrangement and compressed air as the media. The objective is to study the design parameters involved and to evaluate the performance characteristics of the device, comparing theorectical and experimental results. Work was carried out to investigate the blanking of thick gauges of metals using the accelerator developed.